Ementation Of Patient Safety Objectives With Nurse Caring Attitude As A Variable Mediation In Rs-X - Ramli Saibun Hasudungan; Kemala Rita Wahidi; Erry Yudhya (Syntax Corporation Indonesia, 2022)
Patient safety is an important part of health services. Patient safety is determined by the implementation of patient safety goals. Implementation of patient safety goals plays an important role in the prevention and reduction of risks, errors and injuries that may occur during service. The application of optimal patient safety goals can be determined by the nurse's behavioral factors. Nurse behavior is influenced by several factors, namely individual factors, organizational factors, and psychological factors. Research Objectives: This study aims to analyze the relationship between the leadership style of the head of the room and the clinical career leveling of nurses on the application of patient safety goals with the caring attitude of nurses as a mediating variable. Research method: quantitative explanatory because to determine the relationship between variables based on the previous hypothesis that has been put forward by previous researchers. The sample in this study was a total sampling, that is, all the nurses were 80 people. The analysis technique uses path analysis. The results of the study: (1) the leadership style of the ward head significantly affects the caring attitude of nurses; (2) Clinical career leveling significantly influences nurses' caring attitude; (3) The leadership style of the ward head significantly influences the Implementation of Patient Safety Goals; (4) Clinical career leveling significantly affects the implementation of patient safety goals; (5) The caring attitude of nurses significantly affects the implementation of patient safety goals; (6) The leadership style of the ward head indirectly significantly affects the implementation of patient safety goals through the caring attitude of nurses; and (7) Nurse's clinical career leveling indirectly significantly influences the implementation of patient safety goals through nurses' caring attitude.